2018
DOI: 10.1177/0194599818800477
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Medicine in Otolaryngology Part 9: Valuing Health Outcomes

Abstract: Decisions about resource allocation are increasingly based on value trade-offs between health outcomes and cost. This process relies on comprehensive and standardized definitions of health status that accurately measure the physical, mental, and social well-being of patients across disease states. These metrics, assessed through clinical trials, observational studies, and health surveys, can facilitate the integration of patient preferences into clinical practice. This ninth installment in the Evidence-Based M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…Some studies, such as in [9], investigated face and construct validity of direct utility elicitation methods. Liao et al [10], comparing utility values in Taiwan and Sweden, confirm the need of understanding population differences and the same claim is reported in [11]: “Future health state valuations would ideally be based on representative value sets to reflect the different populations within and beyond the currently evaluated countries.” Again, no study targeted Swiss population, and no study reported UCs for the health states after mini-invasive surgery.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Some studies, such as in [9], investigated face and construct validity of direct utility elicitation methods. Liao et al [10], comparing utility values in Taiwan and Sweden, confirm the need of understanding population differences and the same claim is reported in [11]: “Future health state valuations would ideally be based on representative value sets to reflect the different populations within and beyond the currently evaluated countries.” Again, no study targeted Swiss population, and no study reported UCs for the health states after mini-invasive surgery.…”
Section: Introductionmentioning
confidence: 76%
“…Despite patients, of course, are more aware about their health state and how it affects their life, the general population is probably more suitable for analyses that will be used by healthcare policy makers to take decisions that will affect the population as a whole. One motivation for relying in general community values instead of patients’ ones is that patients may develop adapting behaviors to live with a certain heath state, thus overestimating the true state utility [11].…”
Section: Methodsmentioning
confidence: 99%
“…100 A published review of the Tufts CEA registry from 1976 to 2011 revealed that only 2.0% of the CUAs evaluated otolaryngology interventions. 34,39 The study demonstrated a higher proportion of published CUAs in otology (31.1%) than in endocrine surgery (19.6%), sleep medicine/surgery (18.0%), head and neck surgery (13.0%), pediatric otolaryngology (8.2%), allergy (6.6%), and rhinology (3.3%). 100 There were no CUAs related to facial plastics uncovered in their search.…”
Section: Cost-effectiveness Analyses In the Oto-hns Literaturementioning
confidence: 94%
“…36,37,40 QALYs represent the summary measure of a health intervention in terms of time spent in a series of these quality-weighted health states. 38,39,41 Given the multidimensional health outcomes evaluated in surgical interventions, QALYs are commonly used to integrate measures of survival and quality of life. 1,35,40 In the previous example, a patient who takes the chemotherapeutic agent for nasopharyngeal carcinoma may have chronic renal failure as a complication of therapy, which reduces his or her quality of life from 1 to 0.6.…”
Section: Types Of Economic Analysesmentioning
confidence: 99%
“…However, their aim was to investigate face and construct validity of different elicitation methods, and no specific post-surgery states were addressed. Finally, Liao et al [ 17 ] compared utility values ascertained from Taiwan and Sweden, and suggested the need for understanding population differences, which is corroborated by Caulley et al [ 18 ]. As a matter of fact, UCs are subjective measures, and may vary among different populations, depending on cultural, geographical, and economical factors [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 90%